PHYTOCHEMICAL PROFILE OF THE LATEX EXTRACTS OF CALOTROPIS PROCERA (AITON) DRYAND (International Association of Biologicals and Computational Digest, 2022)
Calotropis procera (Aiton) Dryand. is a medicinal plant whose pharmacological properties are associated with its latex. In present study, aqueous and methanolic extracts of the latex were evaluated in an attempt to trace the presence of phytochemicals. The crude latex was diluted in the ratio of 1:10. The results revealed that some phytochemicals exhibited their presence in the aqueous solvent whereas some displayed their presence in the methanol. These findings provide an explanation for the use of different solvents in the experiments of phytochemical screenings.
Keywords: Latex, Aqueous extract, Methanolic extract and Phytochemical constituents